Increase Performance of IPMSM by Combination of Maximum Torque per Ampere and Flux-Weakening Methods. (20th August 2013) - Toosi, Saman; Rezazadeh Mehrjou, Mohammad; Karami, Mahdi; Zare, Mohammad Reza
Abstract : Interior permanent magnet motor (IPMSM) was used as air conditioner compressor to reduce the power consumption and improve the performance of the system. Two control methods including maximum torque per ampere (MTPA) and flux-weakening methods were employed to increase the speed range of the air conditioner compressor. The present study adapted the flux weakening algorithm technique which can be used for constant torque and constant power regions. Results indicated that the operation speed range of the IPMSM may increase significantly by using the proposed flux weakening algorithm.